Evaluation of silent period on masticatory cycles of different muscles in dentate oral contraceptives users and nonusers - Turcio, Karina Helga Leal [UNESP]; Garcia, Alício Rosalino [UNESP]; Zuim, Paulo Renato Junqueira [UNESP]; Moreno, Amália [UNESP]; Goiato, Marcelo Coelho [UNESP]; Guiotti, Aimée Maria [UNESP]; Santos, Daniela Micheline dos [UNESP] (European Journal Of Dentistry, 2015)
The aim of this study was to evaluate the influence of oral contraceptive use on the silent period (SP) of anterior temporal and masseter muscles during the menstrual cycle. Totally, 28 women on reproductive age were selected including 15 nonusers of any hormone and 13 contraceptive users. All patients were dentate without muscular temporomandibular disorders. Electromyography (SP test) of the anterior temporal and masseter muscles was conducted every week during three consecutive menstrual cycles at 1(st) day of menstruation (P1), 7(th) day (P2), 14(th) day (P3) and 21(st) day (P4). The SP values in the anterior temporal and masseter muscles were measured at both sides. The SP values of the right side (13.49 ms) at P2 were significantly different compared to the left side (12.28 ms). However, there was no significant difference on the interactions among the three factors. It can be concluded that the SP values in healthy women in reproductive age may not be influenced by the menstrual cycle with similar results for both muscles.
Keywords: Computerized dentistry; Electromyography; Menstrual cycle; Sexual hormones; Silent period